The Impact of Mobile Banking Adoption, Financial Inclusion Programs, Perceived Services Accessibility, and Trust in Financial Institutions on the Financial Empowerment of Rural Communities - Mesri Welhelmina Nisriani Manafe; Herny Constantia Fanggidae; Fransina Pattiruhu; Helda Marlin Ala; Nitaniel Hendrik (Journal Management & Economics Review (JUMPER), 2026)
This study examines the impact of mobile banking adoption, financial inclusion programs, perceived service accessibility, and trust in financial institutions on the financial empowerment of rural communities. Using a quantitative research design, data were collected through structured questionnaires from 400 adult residents in rural areas. Descriptive statistics, reliability tests, correlation analysis, and multiple regression analysis were conducted to explore the relationships among the variables. The results indicate that all four factors significantly and positively influence financial empowerment, with mobile banking adoption emerging as the strongest predictor. Financial inclusion programs, trust in financial institutions, and perceived service accessibility also contribute meaningfully, highlighting the importance of a multifaceted approach to enhancing financial capabilities in rural populations. The study underscores the need for integrated strategies that combine technology adoption, institutional support, improved service accessibility, and trust-building measures to promote sustainable financial empowerment. These findings provide valuable insights for policymakers, financial institutions, and development practitioners seeking to enhance economic resilience and autonomy in rural communities.